The effect of compensation, discipline and work environment on the performance of State Civil Apparatus (ASN) of the Transportation Service of Parigi Moutong Regency - Sakaria, Maulid; Umar, Muhammad (Goodwood Publishing, 2025)
Purpose: The purpose of this study is to find out how compensation, work discipline, and work environment affect the performance of the State Civil Apparatus (ASN) at the Transportation Service of Parigi Moutong Regency. Research Methodology: The research was conducted at the Transportation Service Office of Parigi Moutong Regency. The study used a descriptive quantitative method with a questionnaire survey given to 49 respondents.The data were analyzed using multiple regression and correlation analysis to measure the relationship and influence between variables. Results: The results show that compensation, discipline, and work environment have a very strong relationship with employee performance, with a correlation coefficient (R) of 0.874. The coefficient of determination (R²) is 0.763, which means that 76.3% of employee performance is influenced by the three variables, while 23.7% is influenced by other factors not studied. Conclusions: Compensation, discipline, and work environment together have a significant and strong influence on the performance of the State Civil Apparatus. Improving these factors can lead to better productivity and work results among employees. Limitations: The study only involved a small number of respondents (49) from one government agency in Parigi Moutong Regency, so the findings cannot be generalized to all public institutions. Contribution: This study contributes to public administration and HR management by showing how internal factors affect employee performance. It can help local governments and policymakers improve management and evaluation practices.